2023
DOI: 10.1177/08404704231182671
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and impacts from wait times for specialist care identified by primary care providers: Results from the MAAP study cross-sectional survey

Abstract: In Canada, primary care providers are the front door to other services in the health system, such as specialist care. Compared to other countries, Canadians experience long wait times for specialist referrals and appointments leading to poorer health outcomes for patients. Although there is attention paid to the impacts of these waits on patients, little is known about how long specialist care wait times impact primary care providers. As part of a larger study surveying primary care clinics in Nova Scotia, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The setting of anticipated workforce shortages, wait times and the referral process for rheumatology services are growing concerns 14 . The referral pathway requires additional support to bridge the gap between referral and clinic review to prevent overburdening ED 30,31 . Participants reported that AHWs provided support in navigating health services and facilitating cross‐cultural communication in the theme 2E.…”
Section: Discussionmentioning
confidence: 99%
“…The setting of anticipated workforce shortages, wait times and the referral process for rheumatology services are growing concerns 14 . The referral pathway requires additional support to bridge the gap between referral and clinic review to prevent overburdening ED 30,31 . Participants reported that AHWs provided support in navigating health services and facilitating cross‐cultural communication in the theme 2E.…”
Section: Discussionmentioning
confidence: 99%
“…The enthusiasm evident in our participants' comments is mirrored by the dramatic increase in appetite for virtual care nationally, 4 and can be contrasted against broader Canadian frustrations with access to primary and specialist care. 5 This study has limitations, including potential bias toward recruiting individuals already comfortable with virtual care, and recruiting radiologists who may be more inclined to provide a positive patient experience. Additionally, participants were not compared with a control group receiving the standardof-care imaging results from their referring physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Radiology reports traditionally serve as the primary means of conveying the results of diagnostic images between radiologists and referring physicians, often resulting in patients receiving a verbal, rather than visual, description of their condition. 4,5 Patient-physician interactions provide an opportunity not only for knowledge translation, but for compassionate and individualized care. The results from this study suggest that VRCCs, which offer expert-guided visual aids, logistical convenience, and valuable patient-radiologist facetime, could significantly improve the patient experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCOPE-MH program is an innovative approach to build capacity in primary care and address lengthy waiting lists and connect primary care to psychiatric specialty to tackle the mental health needs of individuals within the community [ 6 ]. Through this collaborative care program, PCPs are supported and accompanied through the patient’s mental health care journey, exposing PCPs to new resources, treatment modalities and options, and, ultimately, increasing comfort and confidence with treating more complex patients.…”
Section: Introductionmentioning
confidence: 99%